2014
DOI: 10.1007/s11832-014-0600-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for assessing postoperative femoral head reduction in developmental dysplasia of the hip

Abstract: PurposeDevelopmental dysplasia of the hip (DDH) affects approximately 1 % of live births. Dislocated hips require reduction and stabilisation in a spica cast, and reduction efficacy is assessed radiologically. Numerous measurements are used to ascertain the adequacy of reduction but can be inconsistent in evaluating femoral head position. This study describes the morphology of the developing acetabulum in DDH and validates a novel method to assess adequate reduction of the dysplastic hip following closed or op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…The Shenton's line, the outside boundary of the acetabulum, and the sourcil of the acetabulum are subjective diagnostic indicators, and the judgment effect are related to clinical experience. It was also found that the inter-class consistency of Shenton's line was low (−0.01–0.33) ( 30 ). CE angle and acetabular index are the main reference indices for diagnosis of DDH, and from the results of this study, it has shown excellent consistency of surgeons whatever their working years are.…”
Section: Discussionmentioning
confidence: 99%
“…The Shenton's line, the outside boundary of the acetabulum, and the sourcil of the acetabulum are subjective diagnostic indicators, and the judgment effect are related to clinical experience. It was also found that the inter-class consistency of Shenton's line was low (−0.01–0.33) ( 30 ). CE angle and acetabular index are the main reference indices for diagnosis of DDH, and from the results of this study, it has shown excellent consistency of surgeons whatever their working years are.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of dysplasia of the hip (DDH) is about 1:100 live births [1]. With the introduction of screening programs, the incidence of surgical intervention has significantly dropped.…”
Section: Introductionmentioning
confidence: 99%
“…During cast immobilization, surgeons need to accurately assess the status of hip reduction to ensure successful treatment and avoid complications [1]. Radiography [21], CT [3,15], and MRI [4,8,11,12,14] have been used to assess reduction status. However, radiography and CT cannot show the details of cartilage very well, and those modalities are associated with radiation; MRI also has disadvantages, such as the need for sedation, high costs, and long scanning times.…”
Section: Introductionmentioning
confidence: 99%